Beyond Transition: Personal and Social Transformation Through Co-Inquiry Among Military-Connected Students. (May 2021) - Kent, Shannon M.; Buechner, Barton D.
Social reintegration of veterans following military service is a complex, nonlinear, and highly individualized phenomenon, yet much of the existing literature on transition of veterans represents a narrow and limited perspective of transition and trauma—mostly written from an external (nonveteran) perspective. We present an alternative based on concepts of personal and social transformation through collaborative, veteran-led social science research designed from an interdisciplinary Adlerian (social systems) perspective. Participants are military-connected students, defined as service members, veterans, family members, and mental health practitioners experienced in working with military and veteran populations. Research projects described were designed by the students, and these typically involved informal data gathering and self-reflection, combined with extensive review of current interdisciplinary literature in the military psychology field. A case study of informal participative research with a cohort of female Navy Chief Petty Officers by the first author is presented as an example. Conclusions and recommendations support further extension of this cohort-driven adult learning model as a means of combining personal growth and social transformation by including military, veteran, and family perspectives in research and literature directed toward veterans' social and mental health programs and policies.